N5 Is the New C4a: Biochemical Functionalization of Reduced Flavins at the N5 Position - Beaupre, Brett A.; Moran, Graham R. (Frontiers in Molecular Biosciences, 2020)
For three decades the C4a-position of reduced flavins was the known site for covalency within flavoenzymes. The reactivity of this position of the reduced isoalloxazine ring with the dioxygen ground-state triplet established the C4a as a site capable of one-electron chemistry. Within the last two decades new types of reduced flavin reactivity have been documented. These studies reveal that the N5 position is also a protean site of reactivity, that is capable of nucleophilic attack to form covalent bonds with substrates. In addition, though the precise mechanism of dioxygen reactivity is yet to be definitively demonstrated, it is clear that the N5 position is directly involved in substrate oxygenation in some enzymes. In this review we document the lineage of discoveries that identified five unique modes of N5 reactivity that collectively illustrate the versatility of this position of the reduced isoalloxazine ring.